2020
DOI: 10.23937/2690-263x/1710006
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Changes in Alcohol and Substance Use Disorders- An Overview

Abstract: to the nervous system and internal organs. Moreover, illicit drug uses are commonly linked with aplastic anaemia, bone marrow repression and variety of systemic disorders [3]. Hence, early diagnosis of these disorders and identification of the complications they result in is important. Haematology is the branch of medicine that deals with blood, blood-forming organs and blood disorders. This article summarizes current information on the haematological changes that are observed in different substance use disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Mean Hb values exhibited a similar pattern. These results, inconsistent across alcohol concentrations, align with Jain et al’ (2020) findings, suggesting varying effects of alcohol on Hb and its potential to inhibit haematopoiesis, leading to conditions like anemia [ 121 ].…”
Section: Discussionsupporting
confidence: 83%
“…Mean Hb values exhibited a similar pattern. These results, inconsistent across alcohol concentrations, align with Jain et al’ (2020) findings, suggesting varying effects of alcohol on Hb and its potential to inhibit haematopoiesis, leading to conditions like anemia [ 121 ].…”
Section: Discussionsupporting
confidence: 83%
“…Alcohol use disorder can directly and indirectly affect hematological parameters, while chronic opioid use alters blood homeostasis( 37 ). Our findings show that opioid users have low RBC levels and increase MCV, HGB, HCT, and RDW compared to healthy individuals, Alcoholics also have low levels of hemoglobin, RBCs, hematocrit, and platelets, as well as elevated MCV, RDW, and MCH levels( 38 ). Although the impact of these hematological biomarkers on PTSD and adverse events is not yet established, they do impact the quality of life in patients with comorbidities( 39 42 ).…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, cannabis abuse has been shown to have minimal effects on blood indices. Some studies have reported slight decreases in RBC count and hemoglobin levels, but these changes are usually within the normal range and not clinically significant 4 , 5 , 20 . Our results are consistent with these studies showing the possible negative consequences of drug misuse on immunity.…”
Section: Discussionmentioning
confidence: 98%
“…There are direct hematological adverse effects of acute and chronic drug abuse, including toxic effects on bone marrow or other blood-forming organs, leading to lower-than-normal or malfunctioning blood cells. Indirect effects may lead to alterations in metabolic and/or physiological functions, which determine liver and kidney diseases, and nutritional deficiencies, that affect the function of various blood cells 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%